85.0k views
5 votes
2(3x-6)-2x+1=25 solve for x

User Simaglei
by
5.1k points

2 Answers

4 votes

Answer:

X = 6.5

Explanation:

First we need to simplify and also remember the use of PEMDAS.

6x-12-2x+1=25

4x-11=25

Addition property of equality

4x=26

Division property of equality

x=6.5

User Landings
by
4.5k points
5 votes

Answer:

Explanation:

Step 1: Simplify both sides of the equation.

2(3x−6)−2x+1=25

(2)(3x)+(2)(−6)+−2x+1=25(Distribute)

6x+−12+−2x+1=25

(6x+−2x)+(−12+1)=25(Combine Like Terms)

4x+−11=25

4x−11=25

Step 2: Add 11 to both sides.

4x−11+11=25+11

4x=36

Step 3: Divide both sides by 4.

4x

4

=

36

4

x=9

User Sarwar
by
5.1k points